STUDY ON INTEGRATING CHILDREN’S STORIES FOR LEARNING NUMERATION IN ROMANIAN PRESCHOOL EDUCATION - MAGDAȘ, Ioana-Cristina; FARCAȘ, Georgeana; MAGDAȘ, Adrian (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2022)
The new Curriculum for preschool education in Romania, introduced in 2019, launches a challenge for educators: the active involvement of preschoolers in the activities carried out in kindergarten, their preparation for a social life based on cooperation, communication and action. One of the recommendations of the new curriculum is to organize the learning content in an integrated way. In this context, we intended to study how pre-school teachers’ approach in an integrated way the teaching of numeration through stories, their role and importance. The data were collected using the survey method based on a questionnaire in Google Drive. The questionnaire was completed voluntarily and anonymously by 101 teachers for preschool education. Over 88% of respondents consider that stories contribute to a large or to a very large extent to learning the numeration and that preschoolers are actively involved in learning activities in which stories are used, obtaining very good mathematical performances. Almost all preschool teachers who attended the study found the use of stories in learning to be very beneficial, even if they face to some difficulties, including the lack of a collection of consacrated stories for learning numeration. Received: 2022 March 05; Revised: 2022 March 25; Accepted: 2022 March 28; Available online: 2022 May 5; Available print: 2022 May 30